Cardiometabolic Risk Factor in Obese and Normal Weight Individuals in Community Dwelling Men - Kim, Hyunsoo (Int J Environ Res Public Health, 2020)
The aim of this study was to investigate the cardiometabolic risk factors (CRFs) in community dwelling men based on a combination of body mass index (BMI) and waist circumference (WC). This cross-sectional study was based on 867 males between the ages of 20 and 71 years. Subjects were categorized into 4 groups by BMI and WC (Group 1, BMI < 25 kg/m(2) and WC < 90 cm; Group 2, BMI < 25 kg/m(2) and WC > 90 cm; Group 3, BMI > 25 kg/m(2) and WC < 90 cm; and Group 4 BMI > 25 kg/m(2) and WC > 90 cm). The proportion of subjects with a normal weight with high WC was 3.2%. Among normal weight men with the high range of WC, significantly high Odds ratios (ORs) and 95% CI were found for hypertriglyceridemia (3.8, 1.8–8.2) and high blood glucose (3.2, 1.5–6.9). The probability that the general obesity group (Group 3) had one CRF was around twice that of the reference group (Group 1) (1.9 to 2.1 times), but Group 2 had probability more than 4 times higher (4.3 to 4.6 times). In community dwelling adult men, normal weight with high waist circumference was associated with the highest cardiometabolic risk. In conclusion, follow-up screening of those with high WC may be necessary to detect and prevent cardiometabolic diseases, particularly for men with a normal weight.